TanCAR: A Novel Bispecific Chimeric Antigen Receptor for Cancer Immunotherapy - Zakaria Grada; Meenakshi Hegde; Tiara Byrd; Donald R Shaffer; Alexia Ghazi; Vita S Brawley; Amanda Corder; Kurt Schönfeld; Joachim Koch; Gianpietro Dotti; Helen E Heslop; Stephen Gottschalk; et al. (Elsevier, 2013)
Targeted T cells are emerging as effective non-toxic therapies for cancer. Multiple elements, however, contribute to the overall pathogenesis of cancer through both distinct and redundant mechanisms. Hence, targeting multiple cancer-specific markers simultaneously could result in better therapeutic efficacy. We created a functional chimeric antigen receptor'the TanCAR, a novel artificial molecule that mediates bispecific activation and targeting of T cells. We demonstrate the feasibility of cumulative integration of structure and docking simulation data using computational tools to interrogate the design and predict the functionality of such a complex bispecific molecule. Our prototype TanCAR induced distinct T cell reactivity against each of two tumor restricted antigens, and produced synergistic enhancement of effector functions when both antigens were simultaneously encountered. Furthermore, the TanCAR preserved the cytolytic ability of T cells upon loss of one of the target molecules and better controlled established experimental tumors by recognition of both targets in an animal disease model. This proof-of-concept approach can be used to increase the specificity of effector cells for malignant versus normal target cells, to offset antigen escape or to allow for targeting the tumor and its microenvironment.